Fabrication and characterization of a novel acacia gum copolymer for improving graphene-based membrane - Ghany M.A.R.A.; Lun A.W.; Alsaffar M.A.; Mahmoudi E.; Ayodele B.V. (American Institute of Physics Inc., 2023)
Membrane technology has emerged as an alternative to conventional water treatment methods. Membranes, however, are exposed to fouling phenomena during their application. These have contributed to short membrane durability and higher operating cost. Improvements of commercial membrane characteristics and developing new membrane materials, thus, are the focus of membrane researchers in recent years in order to enhance the membrane overall performance. This current study was aimed to develop a composite membrane material with improved characteristics such as high fouling resistance, high flux, high hydrophilicity and good mechanical properties. Graphene oxide (GO) nanoplates have become the best candidate to be adopted as a nanofillers in the membrane matrices owing to its unique properties. Polyethersulfone (PES) membranes have been fabricated using a direct blending of the nanoplates in the blending solution via a wet phase inversion method. The addition of GO nanoplates and acacia gum to the casting solution changed the viscosity of the solution. As a result, the membrane with denser sub-layer and smaller pore size were formed owing to the changes in phase inversion kinetics. All the membranes, however, have an integrated asymmetric structure according to Field Emission Scanning Electron (FESEM) images. Fouling phenomena of the fabricated membranes were quantified by measuring flux declines at constant suction pressure. 2020 Author(s).